2013
DOI: 10.1002/14651858.cd001865.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Personalised risk communication for informed decision making about taking screening tests

Abstract: Analysis 1.11. Comparison 1 personalised risk communication versus general risk information, Outcome 11 smoking. Analysis 1.13. Comparison 1 personalised risk communication versus general risk information, Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
175
0
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(197 citation statements)
references
References 128 publications
3
175
0
9
Order By: Relevance
“…Some published studies have found that communicating tailored messages positively impacts recruitment and engagement, increasing the uptake and referral to these services (17). Proactive engagement of smokers by personalizing the advice and communicating the risk factors tailored to the individual works as a good engagement strategy.…”
mentioning
confidence: 99%
“…Some published studies have found that communicating tailored messages positively impacts recruitment and engagement, increasing the uptake and referral to these services (17). Proactive engagement of smokers by personalizing the advice and communicating the risk factors tailored to the individual works as a good engagement strategy.…”
mentioning
confidence: 99%
“…Other indirect evidence for benefit comes from limited findings of improvements with medical and surgical patients' knowledge related to use of personalized risk communications (Edwards et al 2013) or decision aids (Knops et al 2013). Decisional conflict also shows some reductions related to use of decision aids (Stacey et al 2011).…”
Section: Rationalementioning
confidence: 99%
“…In an arena confusing even to many professionals, we are clearly failing our audience in often achieving patient-professional discussions and online patient education materials of only minimal comprehensibility. Fortunately, patient decision aids based on validated measures of the primary outcome (informed choice) can improve informed values-based choices, patient-practitioner communication, and realistic perception of outcomes while reducing decisional conflict [84][85][86] . One such is the online Breast Cancer Screening Decision Aid (from the Public Health Agency of Canada) [87][88][89] , with its quantitative estimates of major risks and benefits of screening; another is the BreastScreen Australia decision aid 90 , the first mammography screening decision aid validated in a randomized controlled trial 91 .…”
Section: Communicating the Harmsmentioning
confidence: 99%